Pollination of two sympatric species of Stelis (Pleurothallidinae, Orchidaceae) - Albores-Ortiz, Octavio; Sosa, Victoria (Instituto de Ecología, A.C., 2006)
Stelis hymenantha and S. immersa are epiphytic orchids growing sympatrically on oaks in the area of Ocosingo, Chiapas. They belong to the group of Pleurothallidinae, in which pollination by Diptera is frequent. The objective of this paper is to determine pollination system as well as the mechanisms that prevent hybridization between these species. Field work was carried out in order to determine the number of individuals per population, flowering period, fruit set, as well as pollinators, attractants and rewards that the plants of these two species offer. Results indicate that S. hymenantha and S. immersa coincide in flowering during certain period of time, that the flowers have different size and morphology, that both produce fragrances, that are different, and that both produce a ‘‘nectarlike’’ transparent substance on the base of the lip and in one of the species also on the petals. Stelis immersa is pollinated by females of a fly in the genus Megaselia (Phoridae) and receives a large number of visitors. The pollinator of S. hymenantha was not determined precisely, however a Drosophilidae fly was seen entering flowers. Removal of pollinaria is determined by the size of pollinator. A very low number of capsules is produced in both species.